Expecting the unexpected in the search for extraterrestrial life. Issue 6 (6th December 2020) - Vickers, Peter
Abstract: On p. 10 of the 2018 National Academies Exoplanet Science Strategy document (NASEM 2018), 'Expect the unexpected' is described as a general principle of the exoplanet field. But for the next 150 pages, this principle is apparently forgotten, as strategy decisions are repeatedly put forward based on our expectations. This paper explores what exactly it might mean to 'expect the unexpected', and how this could possibly be achieved by the space science community. An analogy with financial investment strategies is considered, where a balanced portfolio of low/medium/high-risk investments is recommended. Whilst this kind of strategy would certainly be advisable in many scientific contexts (past and present), in certain contexts – especially exploratory science – a significant disanalogy needs to be factored in: financial investors cannot choose low-risk high-reward investments, but sometimes scientists can. The existence of low-risk high-impact projects in cutting-edge space science significantly reduces the warrant for investing in high-risk projects, at least in the short term. However, high-risk proposals need to be fairly judged alongside medium- and low-risk proposals, factoring in both the degree of possible reward and the expected cost of the project. Attitudes towards high-risk high-impact projects within NASA since 2009 are critically analysed.